2017
DOI: 10.4103/tjo.tjo_13_17
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcome of deep anterior lamellar keratoplasty with air-assisted manual dissection for corneas with previous inflammation or fibrosis

Abstract: PURPOSE:To report our experience in air-assisted manual dissection deep anterior lamellar keratoplasty (DALK) for the treatment of corneal scar with previous inflammation and fibrosis.MATERIALS AND METHODS:We retrospectively reviewed the medical history of 21 patients (male:female = 13:8 mean age 41.9 years old) with corneal pathology from previous infection and inflammation. Trephination diameter ranged from 7.0 to 8.0 mm, and the graft was oversized by 0.25–0.50 mm. Debulking technique was performed to expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…[ 16 17 ] Many modifications of the technique have also been described and have been useful for DALK. [ 18 19 20 ] In case of a failed big bubble, manual dissection may be required to carry out the stromal dissection. [ 21 ] In our study, we found that DM perforation can occur at any stage of the surgery and the surgeon ought to be extremely careful for the same.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 17 ] Many modifications of the technique have also been described and have been useful for DALK. [ 18 19 20 ] In case of a failed big bubble, manual dissection may be required to carry out the stromal dissection. [ 21 ] In our study, we found that DM perforation can occur at any stage of the surgery and the surgeon ought to be extremely careful for the same.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, big bubble technique, though commonly fails to separate predescemtic plane, effectively creates air-filled stroma, which is easier to remove. 68 Manual DALK by intrastromal air injection had also been described for postherpetic leukoma opacity. It had a safe intraoperative profile and resulted in significant visual recovery.…”
Section: Resultsmentioning
confidence: 99%
“…[ 49 ] Air-assisted manual dissection has demonstrated efficacy in cases of scarring due to inflammation and fibrosis, with confocal microscopy supporting comparable results. [ 8 50 ]…”
Section: Discussionmentioning
confidence: 99%